Live Colonocytes in Newborn Stool: Surrogates for Evaluation of Gut Physiology and Disease Pathogenesis - Chandel, Dinesh S. (2011)
Studies of gastrointestinal pathophysiology are not feasible by biopsies in human neonates. We examined the utility of live colonocytes in stool in studying cellular markers during early neonatal life. Expression of IgA, IgG, Cluster of Differentiation-45 cells (CD45), Toll-like receptors-2 and 4 (TLR2, TLR4) were analyzed by flow-cytometry. Colonocyte RNA extracts were used in quantitative RealTime-PCR (qRT-PCR) to examine the expression of cytokeratin-19, ribosomal protein-24, and tight-junction (Tj) protein zonula occludens-1 (ZO-1). Colonocyte yield varied between 5×10(4) to 2×10(6) cells/g of stool. Meconium samples yielded a highly enriched population of viable cells. Although low, all samples showed CD45-positive cells during the initial weeks of life. Starting as early as day-2, IgA expression was observed in 69% of the cells. Low to moderate expression of IgG was observed with a linear increase as the infants grew. There was an almost total lack of TLR2 staining; however, over 55% of the colonocytes showed TLR4 expression. While high levels of IgA in gut cells may serve as a natural protectant during neonatal period, increased TLR4 may provide a niche for lipopolysacharide (LPS) mediated epithelial damage. Use of stool colonocytes can be a valuable noninvasive approach for studying gut pathophysiology in the neonatal period.